Development Status of TCM Nursing Clinic (中医护理门诊建设发展现状) - DENG Jianhua (邓建华); ZHANG Jing (张敬); TANG Ling (唐玲) (中西医结合护理)
By summarizing the establishment and operation of TCM Nursing Clinic in recent years, the working mode and management method of TCM Nursing Clinic are further discussed in this paper. Ideas and reference are also provided for the sustainable development and standardized operation scheme of TCM Nursing Clinic. (本文通过梳理近年来中医护理门诊的建立和运营, 进一步探讨中医护理门诊的工作模式和管理方法, 为中医护理门诊可持续性发展及标准化运行方案提供思路和借鉴。)